What explains change-supporting behavior within local agenda 21 civil society groups to promote sustainable development? - Zacher, Christoph; Born, Marieke; Wurster, Stefan; Michel, Alexandra (Sustainability, 2021)
Civil society groups and their members are important agents within the multi-stakeholder change process towards more ecological, social, global, and economic sustainability. To better understand civil society group members’ drivers within this complex societal change process, the present study examines the impact of perceived participation, leader-member exchange (LMX), procedural justice, and procedural justice climate on change-supporting behavior. Referring to social exchange theory, data from 125 members of 34 civil society groups that engage in the Agenda 21 process in Germany were gathered by paper/pencil and online questionnaires. Multi-level analyses were conducted to examine interactions between group-level and individual-level phenomena. We found that participation and LMX positively affected group members’ procedural justice perceptions and that procedural justice positively affected group members’ change-supporting behavior. Procedural justice further mediated the relationship between participation, LMX, and change-supporting behavior. The study’s results suggest that fair social exchange processes with civil society group members should be more encouraged by other societal stakeholders (i.e., government, civil society group leaders) wishing to maximize civil society group members’ change-supporting behavior. This study demonstrates ways to promote change initiatives in civil society. Fair social exchange processes help to overcome participation hurdles in the complex field of sustainable local development.